Ofício de guincheiro : análise da atividade dos operadores de guindaste de bordo no complexo portuário do Espírito Santo - Silva, Gustavo Roberto da (2016)
This research-vessel aimed to put in question the crane driver activity, board crane operators at Espirito Santo port complex, with the intention to cast a critical eye on the work processes in the port in order to understand the particularities of this activity from the direct relationship with the craft. The main theoretical intercessors called to foment the analysis were: Yves Clot; Yves Schwartz; Marcelle Duc; Louis Durrive and Christophe Dejours as well as the contributions of Michael Foucault. It was used as a methodological strategy for the production of data the technique of Instruction to the Double, the establishment of an "work analysis group", the latter served as a means of sharing collective experiences on board crane driver work processes, and individual interview with a novice worker. All meetings were recorded and transcribed. The issues raised in this journey involved the following topics: a) training / boar crane driver training; b) the entry of new workers in this role; c) the port labour organization and; d) the productivity and safety of workers. It was noticed, with the analysis, that in the midst of an work organization based on a strong pressure for productivity resulting of the modernization process, there is the production of a sensitive body in the board crane driver work that arises as a key arbiter of choices they make and that is mobilized to deal with the dilemmas in a real work situation. In addition, the board crane driver activity is crossed by an intense collective rapport during the operation that, based on a relationship of trust, harmony and care for life, contributes to the work and to maintain security.